Devenir post-straight ? - Luc Schicharin (Glad!)
This writing experience is part of an artistic process—both personal and scientific—questioning self-ethnographic practice as a creative form. It leads to an aesthetic reflection on the possibility of making a philosophy about the self—“Giving an Account of Oneself”, to use the Judith Butler’s formula— as a conceptual artistic work. As part of the Foucauldian and Butlerian perspective according to which the body is sculpted by discourses, my work proposes to question a body’s capacity to say and to withdraw from oneself, and thus to work its (social) form by the self-writing; in the particular context of this text, I wanted to try my body’s ability to say and withdraw (from) its own heterosexuality.